2018
DOI: 10.1007/s11604-018-0767-7
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound imaging of the anorectal malformation during the neonatal period: a comprehensive review

Abstract: Anorectal malformation (ARM) is classified as low, intermediate, or high; accurate diagnosis of the type during the early neonatal period is important to determine the appropriate initial surgical approach. This review assesses the role of ultrasound examination in the classification of ARM during the neonatal period, with a focus on landmarks on the sonogram, the approach used for sonography, and the optimal examination timing. The following three factors on the sonogram are used for the classification: locat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 38 publications
2
3
0
Order By: Relevance
“…34 This has been also demonstrated by Jonker et al, who showed that the diagnosis was made at a later stage in mild forms of ARM such as a rectoperineal or vestibular fistula, and sometimes ARM remained completely unrecognized, as the only symptom was a chronic constipation. 35 Sharma et al, also observed a high incident of delayed diagnosis, especially among girls in developing countries (37). Our results confirm these findings, and we strongly support the implementation of an interdisciplinary approach with pediatric surgery consultation as a part of the initial examination in cases of unclear anogenital findings to improve outcome.…”
Section: Time Of Diagnosis and Clinical Findingssupporting
confidence: 88%
See 1 more Smart Citation
“…34 This has been also demonstrated by Jonker et al, who showed that the diagnosis was made at a later stage in mild forms of ARM such as a rectoperineal or vestibular fistula, and sometimes ARM remained completely unrecognized, as the only symptom was a chronic constipation. 35 Sharma et al, also observed a high incident of delayed diagnosis, especially among girls in developing countries (37). Our results confirm these findings, and we strongly support the implementation of an interdisciplinary approach with pediatric surgery consultation as a part of the initial examination in cases of unclear anogenital findings to improve outcome.…”
Section: Time Of Diagnosis and Clinical Findingssupporting
confidence: 88%
“…Twenty-five percent of our children had mild forms clinically suggestive of ARM which needed further imaging diagnostics to establish an ARM with certainty, which was similar to the findings of Hosokawa et al, 37 Often there are only mild symptoms like a tendency to constipation with a nearly normal anus. ARM must be ruled out through imaging diagnostics to avoid further complications, especially in girls.…”
Section: Imaging Diagnosticssupporting
confidence: 86%
“…Defining quality scores The criteria for the image quality were defined beforehand by senior radiologists (SR1, SR2) using the quality criteria defined by Son et al [3] and Hosokawaet al [12]: transperineal US was performed with a high-frequency linear array transducer (8 MHz or higher), with a thick coating of gel over the perineum to eliminate air artifacts. The midsagittal plane was identified by the presence of the pubic symphysis and urethra on the same image.…”
Section: Methodsmentioning
confidence: 99%
“…Transperineal ultrasound is used to evaluate anorectal diseases in neonates and infants 11–13 . To our knowledge, there have been no studies on the diagnostic performance of ultrasound for perianal abscesses and fistula‐in‐ano.…”
Section: Introductionmentioning
confidence: 99%
“…Transperineal ultrasound is used to evaluate anorectal diseases in neonates and infants. [11][12][13] To our knowledge, there have been no studies on the diagnostic performance of ultrasound for perianal abscesses and fistula-in-ano. This study aimed to describe the incidence and diagnostic performance of ultrasound for perianal abscess or fistula-in-ano in pediatric patients with perianal inflammation.…”
mentioning
confidence: 99%